2020
DOI: 10.1186/s42238-020-00034-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of naturalistic THC vs. CBD use on recognition memory: a preliminary study

Abstract: The ratio of ∆9-tetrahydrocannabinol (THC) to cannabidiol (CBD) varies widely across cannabis strains. CBD has opposite effects to THC on a variety of cognitive functions, including acute THC-induced memory impairments. However, additional data are needed, especially under naturalistic conditions with higher potency forms of cannabis, commonly available in legal markets. The goal of this study was to collect preliminary data on the acute effects of different THC:CBD ratios on memory testing in a brief verbal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Subjects consuming primarily ∆ 9 -THC -based strains performed worse memory accuracy after use that correlated with blood ∆ 9 -THC levels. In contrast, consuming the combination of CBD and ∆ 9 -THC was not associated with impaired memory [87].…”
Section: Thc Dose Schizophrenic Symptoms Studymentioning
confidence: 69%
“…Subjects consuming primarily ∆ 9 -THC -based strains performed worse memory accuracy after use that correlated with blood ∆ 9 -THC levels. In contrast, consuming the combination of CBD and ∆ 9 -THC was not associated with impaired memory [87].…”
Section: Thc Dose Schizophrenic Symptoms Studymentioning
confidence: 69%
“…There was no difference in concentrations of THC between the two groups, and they showed the same level of memory performance when they were not intoxicated. A study in Colorado found that verbal recognition accuracy decreased after acute use of high-THC strains of cannabis, whereas there was no difference in task performance after strains containing both THC and CBD (T. Curran et al 2020). However, the combined THC and CBD strain group contained significantly less THC than the THC-only strain group; therefore, this improvement could have been due to decreased THC levels rather than the presence of CBD.…”
Section: Introductionmentioning
confidence: 98%
“…Existing research clearly has shown that at least some of the exhilarating, intoxicating, and impairing characteristics of feeling high are driven by the plant’s THC potency levels ( Curran et al, 2020 ; Cuttler et al, 2021 ). Since the molecule’s discovery by Raphael Mechoulam’s lab in 1964 ( Pertwee, 2006 ), THC has been identified within the scientific and medical communities as one of the primary determinants of feeling high ( National Institute on Drug Abuse, 2021 ), and hence, THC is the singled-out molecule upon which current U.S. Cannabis plant legislation is based, with the 2018 Hemp Farming Act (The Farm Bill) arbitrarily defining legal hemp as Cannabis plant variants with less than 0.3% THC potency.…”
Section: Introductionmentioning
confidence: 99%